Efektivitas Breathing Exercise dalam Menurunkan Kecemasan pada Pasien dengan Kanker Paru - Jelang, Destya Wenny; Kariasa, I Made; Yona, Sri (Journal of Telenursing (JOTING), 2024)
The aim of this research is to determine the effectiveness of breathing exercises, which is one of the independent nursing interventions to reduce anxiety in patients with lung cancer. The research method used was a systematic review carried out on journals originating from three databases, namely, ScienceDirect, Scopus and PubMed which were published between 2020-2023. The research results showed that there were seven articles that showed the effectiveness of breathing exercise programs on anxiety in patients with lung cancer. The conclusion obtained is that breathing exercises using the three-ball apparatus exercise technique, ACBT (Active Cycle Of Breathing Technique), ADOPT-Breathing Training and Qigong Breathing Exercise are considered effective in reducing anxiety significantly in patients with lung cancer. Keywords: Breathing Exercise, Anxiety, Lung Cancer